Comparison of Shear Bond Strength of RMGI and Composite Resin for Orthodontic Bracket Bonding. - Soghra Yassaei; Abdolrahim Davari; Mahjobeh Goldani Moghadam; Ahmad Kamaei (Tehran University of Medical Sciences, 2014)
The aim of this study was to compare the shear bond strength (SBS) of resin modified glass ionomer (RMGI) and composite resin for bonding metal and ceramic brackets.Eighty-eight human premolars extracted for orthodontic purposes were divided into 4 groups (n=22). In groups 1 and 2, 22 metal and ceramic brackets were bonded using composite resin (Transbond XT), respectively. Twenty-two metal and ceramic brackets in groups 3 and 4, respectively were bonded using RMGI (Fuji Ortho LC, Japan). After photo polymerization, the teeth were stored in water and thermocycled (500 cycles between 5° and 55°). The SBS value of each sample was determined using a Universal Testing Machine. The amount of residual adhesive remaining on each tooth was evaluated under a stereomicroscope. Statistical analyses were done using two-way ANOVA.RMGI bonded brackets had significantly lower SBS value compared to composite resin bonded groups. No statistically significant difference was observed between metal and ceramic brackets bonded with either the RMGI or composite resin. The comparison of the adhesive remnant index (ARI) scores between the groups indicated that the bracket failure mode was significantly different among groups (P